SPECTROSCOPY IN A ROTATING DEFORMED NUCLEUS - Papadopoulos, C. T.; Vlastou, R. (HNPS Advances in Nuclear Physics, 2020)
Recent advances in the physics of nuclei at high spin are presented. In particular the new phenomena observed by the latest generation of γ-rays spectrometers are discussed. An overview of experimental and theoretical treatment of "backbending·’’ effect, quasiparticle alignment and band crossing is described in more detail. The outlines of the Cranked Shell Model, which is a successful framework for the interpretation of experimental data, are also reported.